Panel 4: Report of the Microbiology Panel - Barenkamp Stephen J; Chonmaitree Tasnee; Håkansson Anders P; Heikkinen Terho; King Samantha; Nokso-Koivisto Johanna; Novotny Laura A; Patel Janak A; Pettigrew Melinda; Swords W Edward (SAGE PUBLICATIONS LTD, 2022)
Objective. To perform a comprehensive review of the literature from July 2011 until June 2015 on the virology and bacteriology of otitis media in children.
Data Sources. PubMed database of the National Library of Medicine.Review
Methods. Two subpanels comprising experts in the virology and bacteriology of otitis media were created. Each panel reviewed the relevant literature in the fields of virology and bacteriology and generated draft reviews. These initial reviews were distributed to all panel members prior to meeting together at the Post-symposium Research Conference of the 18th International Symposium on Recent Advances in Otitis Media, National Harbor, Maryland, in June 2015. A final draft was created, circulated, and approved by all panel members.
Conclusions. Excellent progress has been made in the past 4 years in advancing our understanding of the microbiology of otitis media. Numerous advances were made in basic laboratory studies, in animal models of otitis media, in better understanding the epidemiology of disease, and in clinical practice.Implications for Practice. (1) Many viruses cause acute otitis media without bacterial coinfection, and such cases do not require antibiotic treatment. (2) When respiratory syncytial virus, metapneumovirus, and influenza virus peak in the community, practitioners can expect to see an increase in clinical otitis media cases. (3) Biomarkers that predict which children with upper respiratory tract infections will develop otitis media may be available in the future. (4) Compounds that target newly identified bacterial virulence determinants may be available as future treatment options for children with otitis media.